Modulation of Influenza A virus NS1 expression reveals prioritization of host response antagonism at single-cell resolution - Yang, Qing; Elz, Anna E.; Panis, Maryline; Liu, Ting; Nilsson-Payant, Benjamin E.; Blanco-Melo, Daniel (Frontiers in Microbiology, 2023)
Influenza A virus (IAV) is an important human respiratory pathogen that causes significant seasonal epidemics and potential devastating pandemics. As part of its life cycle, IAV encodes the multifunctional protein NS1, that, among many roles, prevents immune detection and limits interferon (IFN) production. As different host immune pathways exert different selective pressures against IAV as replication progresses, we expect a prioritization in the host immune antagonism by NS1. In this work, we profiled bulk transcriptomic differences in a primary bronchial epithelial cell model facing IAV infections at distinct NS1 levels. We further demonstrated that the intracellular NS1 levels in-part shapes the host response heterogeneity at single cell level. We found that modulation of NS1 levels reveal a ranking in its inhibitory roles: modest NS1 expression is sufficient to inhibit immune detection, and thus the expression of pro-inflammatory cytokines (including IFNs), but higher levels are required to inhibit IFN signaling and ISG expression. Lastly, inhibition of chaperones related to the unfolded protein response requires the highest amount of NS1, often associated with later stages of viral replication. This work demystifies some of the multiple functions ascribed to IAV NS1, highlighting the prioritization of NS1 in antagonizing the different pathways involved in the host response to IAV infection.